PENGARUH IRIGASI DAN PERUBAHAN IKLIM TERHADAP USAHATANI PADI SAWAH DI DAERAH IRIGASI PEKIK JAMAL KABUPATEN KULON PROGO - , BAMBANG SAROSA, IR.,MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Availability of irrigation water causes changes occur in the cropping pattern and cropping intensity. These changes will lead to changes in the use of farm inputs which in turn will lead to changes in income, and the possibility of changes in income distribution. This study aims to analyze: (i) the effect of irrigation on cropping intensity, (ii) the effect of irrigation on rice production, (iii) the effect of irrigation on paddy rice farm income, (iv) the effect of irrigation on income distribution lowland rice farming, (v) influence on the distribution of irrigated rice land tenure, and (vi) the effect of climate change on planted area, production and productivity of paddy rice. The basic method used in this research is descriptive analytical method. The experiment was conducted at the Pekik Jamal Irrigation Area that was in Kulon Progo Regency, Yogyakarta Province. The type of data used is primary data, interviews with farmers using a sample list of questions that have been prepared and secondary data years 1980 - 2011 in the form of rainfall, acreage, production, and productivity. The analytical method used is multiple regression analysis and trend. The results showed that the Irrigation yell Jamal increase cropping intensity. Upland irrigated rice cropping intensity 31% higher than the downstream. While in the nonirrigated rice field area 84% higher. Production of paddy rice farming is affected by the use of chemical fertilizers (Urea, TSP, KCl, ZA, and Ponska) and the use of human labor (labor within the family and outside the family labor). Rice production on irrigated land is higher than the 0.44% non-irrigated paddy production (rainfed) rice production and farmers in the irrigated areas upstream 0.53% higher than the farmers in irrigation areas downstream. Factors that affect the paddy rice farm income was broad land, the price of chemical fertilizers, machinery and labor. Income of farmers on irrigated land is 0.76% higher than the income of farmers in non-irrigated paddy fields (rainfed) and income of farmers in the irrigated areas upstream 0.88% lower than the farmers in irrigation areas downstream. Furthermore, the distribution of income and tenure paddy farmers in irrigated fields more evenly distributed when compared with rainfed land (non-irrigated). Gini ratio value of rice farming income on irrigated land and 0.7133 for non-irrigated paddy fields (0.7081) while the value of Gini ratio of land tenure on land irrigated paddy rice fields 0.7087 and non-irrigated (0.6869). Thus, improving irrigation paddy rice farming income distribution and the effect on the distribution of paddy land tenure. During the period 1980-2011 there is an increase in harvested area, production and productivity of paddy rice. The more extreme type of climate will adversely affect the harvested area, production and productivity of paddy rice. Keywords: cropping intensity, production, income, income distribution, climate change